Voiles et caravansérails : l’Orient dans Lolita - Monica Manolescu (Sillages Critiques)
The Oriental paradigm in Vladimir Nabokov’s Lolita is both explicit (Oriental elements crop up regularly in the novel) and diffuse, in the sense that it offers a model for the development of spatial and narrative progress in the text. Several obvious Oriental motifs could be mentioned: the harem, the pubescent concubine, the oriental decorations of Quilty’s and Gaston Godin’s homes, the imaginary fresco at the Enchanted Hunters, American motels compared to caravansaries, the veil that allows Humbert to catch furtive glimpses of the nymphet’s body. Quilty quotes from the Rubayat, while Humbert refers to the Arabian Nights. The quest for the nymphet is occasionally formulated in terms of Oriental imagery, seen and invented from a European perspective, which allows Humbert to camouflage the moral issue at stake in his relationship with Lolita. Nabokov’s Oriental intertexts, which have not at all been analysed by critics, can be found in Ada as well (although this paper will only focus on Lolita).Going beyond these obvious motifs, Lolita’s Oriental paradigm can also be uncovered, more subtly, in what we could call the “spatial narrative” or “narrative of space” that Humbert invents for the nymphet’s delight when the two of them “put the geography of the United States into motion”. Their trips across the United States are presented as an endless postponing of the fatal ending, as fragmented narratives interrupted by pauses and breaks – just like the Arabian Nights. Moreover, the fundamental association between narrative and sensuality brings together Lolita and the Arabian Nights. Humbert compares himself to a sultan several times, but, upon closer scrutiny, it turns out that he is rather Sheherazade, who needs to invent new appealing stories to amuse Lolita and to keep her close to him. In this sense, Humbert’s model is Proust’s Marcel in The Prisoner, who confesses that, in order to prevent Albertine from running away, he needs to deploy “more ingeniousness than the Persian narrator”.